TANGGUNG JAWAB HUKUM EMITEN ATAS KETERBUKAAN INFORMASI DALAM PENAWARAN UMUM BERBASIS TEKNOLOGI DIGITAL DI PASAR MODAL INDONESIA - Adolf Fictor; Paltiada Saragi; Kadek Jaya Kusumantara; Deni Firwandi; Huske Dwi Gustian; Poltak Maruli Immanuel; Monaliza Kalalembang (Honeste Vivere, 2026)
The development of digitalization in capital market activities has transformed the public offering mechanism from a conventional pattern to an electronic system that relies on the rapid, broad, and integrated delivery of information. This condition has given rise to the need for certainty regarding issuers’ legal responsibilities in fulfilling the principle of information disclosure to potential investors. This study discusses how issuers’ legal responsibilities for information disclosure in digital technology-based public offerings are regulated and the forms of accountability that can be imposed in the event of a violation of this obligation. The research method used is normative legal research with a statutory regulatory approach, a conceptual approach, and a case approach through a review of primary and secondary legal materials, as well as relevant literature. The results show that issuers’ information disclosure obligations are regulated by Law Number 8 of 1995 concerning Capital Markets and the Financial Services Authority regulations governing public offerings and the delivery of information through electronic means. Issuers are required to provide information that is true, complete, accurate, and not misleading. If information is not provided in accordance with the provisions of this Act, the issuer may be held civilly liable, subject to administrative sanctions, and potentially face criminal consequences in accordance with applicable regulations. The findings also show that the use of digital platforms increases the efficiency of information access but also increases the risk of errors, delays, and electronic data manipulation. It is concluded that consistent implementation of the principle of information transparency is a crucial element in protecting investors, maintaining market integrity, and strengthening public trust in the digital capital market ecosystem in Indonesia.